Partisipasi olahraga karyawan perhotelan Kota Pontianak pasca pandemi Covid-19 - B, Putra Sastaman (Universitas Hamzanwadi, 2023)
Employee sports participation in increasing immunity should be a concern for hotel management, especially in the current post Covid-19 pandemic conditions. This study aims to reveal how high the level of sports participation of hotel employees in Pontianak City after the Covid-19 pandemic. This research uses a qualitative research design whose research results are in the form of percentage calculations. Sampling uses control data on the number of hotel employees in Pontianak City. Data collection techniques using questionnaires and observation. The results showed 98.27% of respondents who liked sports and those who did not like to participate in sports amounted to 1.73%. Furthermore, the results showed as many as 91.91% of respondents who did sports in the last 1 week and 8.09% of respondents who did not do sports in the last 1 week. The conclusion is that the level of participation of hotel employees in Pontianak City who like to exercise and respondents who do exercise in the past 1 week is very good.